Initial psychometric evaluation of the Arm Activity Measure (ArmA): a measure of activity in the hemiparetic arm. (August 2013) - Ashford, Stephen; Turner-Stokes, Lynne; Siegert, Richard; Slade, Mike
Objective: To evaluate the psychometric properties of the Arm Activity Measure (ArmA), a patient-reported measure of active and passive function in the paretic upper limb. Design: Psychometric evaluation study. Setting: Two specialist rehabilitation and spasticity management services. Method: Patients ( n = 92) with upper limb paresis were recruited from two specialist neurorehabilitation centres. Mean age 44.5 (SD 16.7). Diagnostic distribution: stroke 48 (52%); other brain injury 28 (31%); or other neurological condition 16 (17%). Evaluation of convergent and divergent validity; unidimensionality, scaling, reliability (internal consistency and test–retest); responsiveness to change and feasibility of the ArmA were undertaken. Results: Expected convergent and divergent relationships were seen with the Leeds Adult Spasticity Impact Scale and the Disabilities of Arm Shoulder and Hand (DASH) (rho 0.5–0.63). Principal components analysis confirmed that active and passive function formed two separate constructs in each sub-scale. Mokken analysis corroborated the findings of the principal components analysis and demonstrated scaling using the monotone homogeneity model (Item H>0.5 for all items). Cronbach's alpha was 0.85 and 0.96, respectively, for the passive and active function subscales. Item level test–retest agreement ranged from 92-97.5% (quadratic-weighted Kappa 0.71-0.94). In the subgroup treated for spasticity with botulinum toxin ( n = 58), the ArmA passive function scale identified a significant difference between responder and non-responder groups (Mann Whitney U = 0.85, p < 0.01). Respondents reported the ArmA to be relevant (77%), easy to use (90%) and timely to complete (83% under 10 minutes). Conclusion: The ArmA is a valid and reliable tool feasible for use in the evaluation of upper limb function in the context of treatment for spasticity.